Determining Knowledge, Attitudes and Practices of HIV and AIDS Among AYA at a Training Institute and Non-Governmental Organization - Musonda, Lucky (International Journal For Research In Social Science And Humanities, 2021)
The propagation of HIV and AIDS in Sub-Saharan Africa raises greater concerns despite availability of interventions. Of concern, are Adolescents and Young Adults (AYA) who share part of the infected population due to this group’s vulnerability to HIV. The study aimed at determining knowledge, attitudes and practices (KAPS) of HIV and AIDS among AYA at a training institute and non governmental organization. The study was descriptive in nature, with 94 students’ respondents from the training institute and 2 representatives, at a non-governmental organization. The study finding found that there were 89.4% respondents with knowledge about how to avoid contracting HIV and AIDS. However, individual expression of high knowledge levels about HIV and AIDS do not necessarily translate into behavioral change or actions but would be effective when coupled with intervening good practices and attitudes. The practices of people disclosing their HIV status could be an indication that it leads to behavior change and prevention of HIV and AIDS. When people’s attitudes towards People Living with HIV and AIDS (PLWHA) have zero stigma, studies indicate that such may lead to increased access to existing services regarding HIV and AIDS that may achieve the 90%90%90% by 2030 in all population groups especially the AYA. Therefore, it would be significant that HIV and AIDS programming are aimed at ensuring that what works in reducing the prevalence is adhered to as failure may lead to upsetting the success made in reduction of infections.